Determinants of Innovative Work Behavior with Learning Agility as a Mediating Variable - Tapi Rondang Ni Bulan; Ani Murwani Muhar; Hafriz Rifki Hafas (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Innovative work behavior is increasingly recognized as a critical factor in enhancing organizational effectiveness and sustainability, particularly in educational institutions facing dynamic environmental changes. This study aims to analyze the effects of work engagement on innovative work behavior and learning agility, as well as to examine the mediating role of learning agility in the relationship between work engagement and innovative work behavior. A quantitative descriptive approach was employed using survey data collected from 200 employees working in educational foundations across North Sumatra, Indonesia. Data were gathered through structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling with SmartPLS software. The findings reveal that work engagement has a significant positive effect on learning agility and innovative work behavior. However, learning agility does not significantly influence innovative work behavior and cannot mediate the relationship between work engagement and innovative work behavior. These results indicate that employees’ engagement with their work directly promotes innovative behavior, whereas learning agility does not serve as a significant explanatory mechanism in this context. This study contributes to the literature by providing empirical evidence from educational foundation employees in Indonesia and offers insights for managers seeking to enhance employee innovation through greater work engagement.